The Role of Mesenchymal Stem Cell Secretome (Extracellular Microvesicles and Exosomes) in Animals’ Musculoskeletal and Neurologic-Related Disorders - Alefe Luiz Caliani Carrera; Bruno Watanabe Minto; Patrícia Malard; Hilana dos Santos Sena Brunel (Veterinary Medicine International)
The advances in regenerative medicine are very important for the development of medicine and the discovery of stem cells has shown a greater capacity to raise the level of therapeutic quality while their use becomes more accessible, especially in their mesenchymal form. In veterinary medicine, it is not different. The use of those cells, as well as recent advances related to the use of their extracellular vesicles, demonstrates a great opportunity to enhance therapeutic methods and ensure more life quality for patients, which can be in clinical or surgical treatments. Knowing the advances in these modalities and the growing clinical and surgery research and demands for innovations in orthopedic and neurology medicines, this paper aimed to review the literature about the methodologies of use and applications such as the pathways of action and the advances that were postulated for microvesicles and exosomes derived from mesenchymal stem cells in veterinary medicine, especially for musculoskeletal disorders and related injuries.